A Review of Two Nanocomposite Insulating Materials Models: Lewis’ Contribution in the Development of the Models, their Differences, their Similarities and Future Challenges - Danikas, M.; Bairaktari, Α.; Sarathi, R.; Basri Bin Abd Ghani, A. (Engineering, Technology & Applied Science Research, 2014)
Nanocomposite polymers are nowadays a major field of research. This paper investigates the interpretational possibilities of two models developed, namely, Tsagaropoulos’ model and Tanaka’s model. Particular emphasis is given to Lewis’ model, which was the first one to be proposed and whose contribution to the aforementioned models was significant. The two models were developed separately and independently from each other. They both consider various layers around the nanoparticles. They both consider well bonded and more loosen layers. Similarities and differences between the two models are pointed out and discussed as well as possibilities for further research in order to shed light on some aspects of electrical phenomena in these materials. Particular emphasis is given to the interfaces between the nanoparticles and the surrounding base material. Comments are offered regarding the challenges facing the two models w.r.t. the interpretation of discharges on nanocomposite surfaces. Possible new areas of research are suggested and new challenges for the aforementioned models are pointed out.